Principles and clinical applications of liquid chromatography — tandem mass spectrometry for the determination of adrenal and gonadal steroid hormones - Kulle, A. E.; Welzel, M.; Holterhus, P.-M.; Riepe, F. G. (Journal of endocrinological investigation, 2011)
Liquid-chromatography — tandem mass spectrometry (LC-MS/MS) is becoming the method of choice for clinical steroid analysis. In most instances, it has the advantage of higher sensitivity, better reproducibility and greater specificity than commercial immunoassay techniques. The method requires only minimal sample preparation and a small sample volume. Furthermore, it has the potential to analyze multiple steroids simultaneously. Modern instruments guarantee high throughput, allowing an affordable price for the individual assay. All this makes LC-MS/MS an attractive method for use in a clinical setting. Reliable reference ranges for the detected analytes are the pre-requisite for their clinical use. If these are available, LC-MS/MS can find application in congenital disorders of steroid metabolism, such as congenital adrenal hyperplasia, disorders of sex development and disorders of salt homeostasis, as well as in acquired disorders of steroid metabolism, such as primary aldosteronism, Cushing’s disease, Addison’s disease, and hyperandrogenemia, as well as in psychiatric disease states such as depression or anxiety disorders. The principles of LC-MS/MS for steroid measurement, the pros and cons of LC-MS/MS compared with conventional immunoassays and the possible applications in clinical routine, with a special focus on pediatric endocrinology needs, are discussed here.